The Effectiveness of Using YouTube Video Based Learning Media on Class XI Students' Interest in Learning at MA Nurul Cholil 2 Galis - Imron, Amin; Ernwati, Ernwati; Mawardi, Imam (FKIP-Universitas Riau, 2024)
Based on observations by researchers in class XI MA Nurul Cholil 2 Galis, the problem found was that the majority of students still paid little attention to learning. This is because it still uses old media such as blackboard, which is patterned learning still monotonous towards the teacher. The aim of this research is to determine the effectiveness of using YouTube video based learning media on class XI students' interest in learning at MA Nurul Cholil 2 Galis. The type of research used in this research is quantitative descriptive research because the data analysis technique uses descriptive statistics. The results of the research show that the data analysis of the implementation of the lesson plan obtained a score of 4.75, the student response questionnaire obtained a score of 89.73% and the student learning outcomes test obtained a score of 81.25%. Based on the results of the data analysis, it can be concluded that the use of YouTube video-based learning media is effectively used in the learning process and is effective in increasing students' interest in learning. This can be seen from the classical student learning completeness score which is at 81.25% and in accordance with the classical student learning completeness indicator if it reaches ≥ 80% so it can be said that the use of learning media is based on YouTube videos are effectively used in the learning process of class XI students at MA Nurul Cholil 2 Galis.